Deciphering climate variability trends: unveiling the impact on household staple crop productivity in East Wallaga Zone, Ethiopia - Kumsa, Dereje Chimdessa; Tesso, Admassu; Tolera, Dereje (Frontiers in Climate, 2024)
This study looks at how Ethiopia’s East Wallaga Zone’s staple crop yields are affected by climate variability between 1990 and 2022. The main goal is to evaluate the effects of temperature and precipitation variations on the production of important crops, namely wheat and teff, in the highlands, midlands, and lowlands of various agroecological zones.The Ethiopian Meteorological Institute, CHIRPS, and TerraClimate were the sources of the climate data used to provide a thorough picture of the trends in temperature and precipitation during the study period. Significant spatiotemporal changes in the research area’s climate patterns were found through data analysis. To measure these fluctuations, important metrics like precipitation concentration, rainfall anomaly indices, and coefficients of variation were computed. Crop yield data from the Zonal Agricultural Office was also used in the study. A regression model was used to examine the association between climatic conditions and crop yields. With a response rate of 95% and a sample size that contained information from each of the three agroecological zones, strong statistical analysis was guaranteed.An 8.2% coefficient of variation in precipitation is one of the significant findings, indicating subtle but important changes in rainfall patterns, namely in the quantity and timing of wet days. Furthermore, a discernible rise in both minimum and maximum temperatures has occurred, particularly in lowland regions, and this has had an additional impact on crop yield.The research comes to the conclusion that although meteorological conditions have a major influence on crop yields, non-climatic factors including soil fertility, agronomic techniques, and technology improvements also have a major impact. The study suggests a three-pronged strategy to reduce the negative effects of climate change on agriculture: raising fertilizer use, strengthening agronomic practices, and increasing soil fertility. The report also emphasizes how important it is to combine measures for adapting to climate change with initiatives to resolve political unrest and advance sustainable agricultural methods.It is recommended that policymakers give equal weight to measures aimed at mitigating and adapting to climate change in order to enhance agricultural productivity and guarantee food security in the area. In East Wallaga Zone and elsewhere, this strategy is crucial for improving lives and feeding the constantly expanding population.